Transplant / Doctoring / Cancer Season - Andersen, Sarah Kristin (Ars Medica, 2019)
Transplant speaks to choices that have to be made, while Doctoring looks at how the persona changes to adapt to the changes between home and work, and Cancer Season compares the progress of cancer to a certain time of the year.